Agreement of the silent partnership – tax and legal consequences of its conclusion and execution - Monika Zieniewicz (Prawo Budżetowe Państwa i Samorządu, 2016)
The institution of the silent partnership is not currently regulated by any legal act in the Polish legal system, although its importance in practice is not in doubt. As every action made in the economic sphere and economic execution of the contract is associated with specific effects on the basis of the tax laws. However, due to the lack of statutory regulation of the institution of silent partnership problematic is the question of determining the effects of tax legislation. Therefore, special attention is needed to determine the issue of these effects on the basis of income tax, tax on goods and services, transfer tax and the tax on inheritance and donations, as well as the question of liability for the tax liabilities of the silent partnership.